Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1182/blood.v45.2.263.263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific hemoglobins within individual erythrocytes

Abstract: The identification of specific antibodies for a variety of inherited hemoglobin variants presents the opportunity to develop sensitive immunochemical measurement techniques for such variants. In this study antibodies specific for human hemoglobins A1 and S were isolated from immune rabbit serum. These were labeled with either fluoroscein isothiocyanate or tetramethylrhodamine isothiocyanate. Erythrocytes suspended in agar were incubated with these labeled antibodies and hemoglobins A1, S, and F were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1977
1977
1983
1983

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The phenomenon of intercellular heterogeneity in the levels of a particular protein within single red cells has also been observed in the distribution of fetal hemoglobin (Hb F) in red cells from adult humans. Using either immunological or alkali-denaturation studies, it has been shown that low levels of Hb F are heterogeneously distributed in red cells from normal adult humans (Shepard et al, 1962;Dan" and Hagiwara, 1967;Headings et al, 1975;Boyer et al, 1975). Heterogeneity in the levels of lib F in single erythrocytes has also been observed in individuals heterozygous for Hb S Wood et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of intercellular heterogeneity in the levels of a particular protein within single red cells has also been observed in the distribution of fetal hemoglobin (Hb F) in red cells from adult humans. Using either immunological or alkali-denaturation studies, it has been shown that low levels of Hb F are heterogeneously distributed in red cells from normal adult humans (Shepard et al, 1962;Dan" and Hagiwara, 1967;Headings et al, 1975;Boyer et al, 1975). Heterogeneity in the levels of lib F in single erythrocytes has also been observed in individuals heterozygous for Hb S Wood et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Μετά άπό λύση τοϋ κυττάρου, τό αντιγόνο διαχέεται κυκλικά καί δημιουρ γεί κατακρημνίσματα, πού μπορούν νά ανιχνευθούν μέ μικροσκοπία σκοτεινού πεδίου. 'Εάν τά αντισώματα είναι συνδεδεμένα μέ φθορί ζουσα ουσία τά κατακρημνίσματα είναι ορατά καί μέ φθορίζουσα μικροσκοπία(52). *Η μελέτη των παρασκευασμάτων γίνεται μέ μικροσκόπιο φθορι σμού τύπου Zeiss μέ σύστημα φωτισμού εκ των άνω καί φίλτρα κα τάλληλα γιά φθορεσκεϊνη ή ροδαμίνη.…”
unclassified